ANALYSIS OF SELF-CONFIDENCE LEVELS AMONG NINTH-GRADE STUDENTS AT MTSs AL-ASYIROT USSYAFIIYYAH - Adinda Nisa Apriati; Indra Budiman (EMTEKA: Jurnal Pendidikan Matematika, 2026)
This study aims to analyze the contribution of ethnomathematics in contextual mathematics learning to the development of junior secondary students’ mathematical reasoning and problem-solving skills using a Systematic Literature Review (SLR) approach following the PRISMA 2020 framework. A total of 15 selected articles were analyzed qualitatively based on relevance, recency, and full-text availability criteria. The results indicate that ethnomathematics is implemented through the exploration of local culture, integration of mathematical concepts into real-life contexts, and the development of contextual learning media. This approach supports the development of mathematical reasoning and enhances problem-solving skills through reflective processes. Furthermore, it creates more meaningful learning experiences, increases students’ motivation, and strengthens conceptual understanding. These findings provide an empirical basis for developing innovative, contextual, and culturally relevant mathematics learning. Kepercayaan diri (self-confidence) merupakan keyakinan individu terhadap kemampuannya dalam mengambil keputusan dan menyelesaikan tugas akademik. Penelitian ini bertujuan untuk menganalisis tingkat kepercayaan diri siswa kelas IX di MTs Al-Asyirotussafiiyyah dalam pembelajaran matematika menggunakan pendekatan kualitatif deskriptif. Instrumen yang digunakan berupa angket dengan indikator 1)percaya pada kemampuan diri sendiri; 2)bertindak mandiri dalam mengambil keputusan; 3)memliki konsep diri yang positif; 4)berani mengungkapkan pendapat. Hasil penelitian menunjukkan bahwa sebagian besar siswa masih kurang percaya diri terhadap kemampuan mereka, meskipun ada yang memiliki rasa percaya diri lebih tinggi. Kepercayaan diri terbukti memengaruhi keberhasilan pembelajaran matematika, sehingga diperlukan upaya untuk meningkatkannya